Propriedades tecnológicas e antimicrobiana de biofilmes de proteínas de peixe com óleo essencial de cravo. - SILVA, Wagner Barreto da (Universidade Federal do Pará, 2022)
The objective of this work was to evaluate the antimicrobial capacity of biofilms elaborated with proteins extracted from filleting residues of gilt (Brachyplatysoma roussauxii) added with essential oil of clove (Eugenia caryophyllata), besides analyzing the technological properties of the films. Two biofilms were prepared, one with 2% of myofibrillar proteins extracted from fillets and the other with 2% of gelatin of the skin of gilt, by the casting method. The concentrations of clove essential oil were 0% (white), 1%, 1.5% and 2% relative to the volume of solution. In the films, the antimicrobial activity was evaluated by the disc-diffusion method and mechanical analyzes (elongation and tensile strength), barrier (permeability to water vapor, water solubility and swelling index), thickness, color and characteristics morphological and structural analyzes using scanning electron microscopy (SEM). Myofibrillar proteins and gelatins extracted from gilt shavings and skin are excellent raw materials for application in biofilms, with protein content of 94.92% and 79.67% and yield of 14.10% and 32.92%, respectively. The biofilms added clove essential oil presented excellent values of water vapor permeability and high elongation values contributing to a better application in food, as well as yellow coloration with low intensity. The biofilms of myofibrillar proteins had an inhibitory effect on the concentrations used against Gram positive bacteria, Staphylococus aureus and Enterococus fecalis. Gelatin biofilms added with OEC did not inhibit the growth of Gram-positive and Gram-negative bacteria.